Understanding wildlife distribution in the human-dominated landscape of Nepal:implications for conservation - Paudel, Prakash Kumar (Jihočeská univerzita, 2012)
In this thesis, I have first reviewed biodiversity status and its conservation in Nepal, which indicates the need of linking the gaps between research and conservation of rare and endangered flora and fauna. Using three mountain ungulates as model species (barking deer - Muntiacus muntjak, Himalayan goral - Naemorhedus goral and Himalayan serow - Capricornis thar), I have investigated effects of human disturbances on wildlife distribution in the human-dominated landscapes of western Nepal, spanning from the subtropical Bardia National Park to the mountainous Shey Phoksundo National Park. I have developed habitat suitability maps for these three ungulate species and recommended a conservation priority area for their conservation. A special emphasis was placed on the study of the distribution of Himalayan serow using different factors related to habitat fragmentation, hunting and patch characteristics and connectivity of forest in midhills landscape of Nepal. Finally, wildlife hunting pattern in the region was investigated in order to explore wildlife conservation issues from the social perspective.
Understanding wildlife distribution in the human-dominated landscape of Nepal:implications for conservation
Keywords: Nepal; biodiversity; physiography; ecoregion; Himalaya; wildlife conservation; habitat fragmentation; connectivity; patch; Nepal; biodiversity; physiography; ecoregion; Himalaya; wildlife conservation; habitat fragmentation; connectivity; patch